EFFECT OF NITROGEN ON SEED COTTON YIELD AND FIBER QUALITIES OF COTTON (GOSSYPIUM HIRSUTUM L.) CULTIVARS - M. F. Saleem; M. F. Bilal; M. Awais; M. Q. Shahid; S. A. Anjum (Journal of Animal and Plant Sciences, 2010)
Seed cotton yield and fiber qualities may be significantly altered by a number of agronomic practices. The present study investigates the effect of nitrogen levels on cotton cultivar's seed cotton yield and fiber quality traits. Three cotton cultivars (NIAB-111, CIM- 496 and FH- 901) were tested against four nitrogen levels (0, 60, 120 and 180 kg ha-1) to check reliability, the highest yielding and good quality fiber traits variety. Varieties differed non significantly with respect to boll weight and seed cotton yield. Similarly nitrogen levels did not exhibit significant effects on fiber quality traits except the lint percentage. Among the three varieties NIAB-111 showed maximum fiber strength, fiber fineness and fiber elongation followed by CIM-496, whereas FH-901 found to have low fiber strength, fiber fineness and fiber elongation and 120 kg N ha-1
Keywords: Cotton cultivars; nitrogen; boll load; yield; fiber qualities was proved to be the best nitrogen level for